Identifikasi Pteridophyta Di Kawasan Leang-Leang Maros Sebagai Sumber Belajar Biologi - GH, Muliana (Peneliti.net, 2025)
This study aims to identify the types of Pteridophyta (ferns) found in the Leang-Leang area, Maros, and to examine the potential of these identified species as biological learning resources. The Leang-Leang area is one of the karst regions in South Sulawesi known for its high biodiversity, including naturally growing ferns in humid and rocky environments. The research employed an exploratory method. Data were collected through direct field observation, documentation, and identification. The results showed that there are six species of Pteridophyta in this area, namely Adiantum philippense L., Lygodium venustum Sw., Phymatosorus scolopendria, Drynaria laurentii, Pteris biaurita L., and Hypodematium crenatum, all of which belong to the class Filicinae. These ferns hold great potential to be used as contextual learning resources in biology education, particularly in topics related to biodiversity and the classification of living organisms.